PENGEMBANGAN KONSEP MATA PELAJARAN TERPADU (Telaah Filsafat Ilmu) - Muhamad Jaeni (Jurnal Forum Tarbiyah, 2011)
Abstract: There is a thought that the moral crisis that occurred inour students one of them is caused by the inappropriate curriculumconcepts given. Existing curricula tend to be oriented to thedevelopment of intellectual and less attention to the development ofthe moral aspects (affective domain). Another factor is the design ofthe curriculum tends to be partial. It means that the realm of scienceand moral aspects are separated according to subjects. Mathematics,Science, Chemistry, Economics, etc are the types of special subjectsdeliberately given to the students to equip science. While thedevelopment of moral and personality assumed by some teachers /educators as the duty of the subjects of Religion, character, citizenship,and other similar subjects. Likewise, philosophically, the curriculumexisted today are not integrated nor based on the concept of human(students). In anticipation of these problems above, a concept ofintegrated subjects is needed. It is the concept of subjects containingknowledge resulting from the study of philosophical formulations whichcontained a full and comprehensive knowledge. The formulation ofknowledge contained on these subjects includes not only theknowledge that examined ontologically, but also includes assessedknowledge epistemologically and axiologically. The concept ofintegrated lessons is also supportive to the efforts of developing theconcept of subjects based on students’ potential. This concept isexpected to equip children as a whole, that is educating the children who will not only have knowledge, but possessing good manners aswell.